The Flip Side of Economic Growth – Predictions from Indonesia - Irwansyah Irwansyah; Ardi Paminto; Zainal Ilmi; Dio Caisar Darma; Yana Ulfah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Special attention in the future will emphasize patterns or studies that are relevant and new in highlighting sustainable economic growth. We seek to identify the role of factors outside of fiscal and monetary policy on economic growth in Indonesia, such as happiness, demographic pressures, labor force, and human development. For this purpose, the OLS method has presented time-series data (2015-2019). Prediction studies show that happiness, demographic pressures, and human development can increase economic growth in a significant direction. Another finding is that the labor force cannot significantly control economic growth, slowly decreasing growth with a negative slope. Practical contributions to developing countries can account for endogenous (internal) growth over the long term. The quality of human resources must prioritize productivity, income, and real welfare. The government needs to plan a policy framework oriented to the fiscal and monetary side.How to Cite:Irwansyah, I., Paminto, A., Ilmi, Z., Darma, D. C., & Ulfah, Y. (2022). The Flip Side of Economic Growth – Predictions from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 107-124. https://doi.org/10.15408/sjie.v11i1.20280.